2014
DOI: 10.1111/nhs.12149
|View full text |Cite
|
Sign up to set email alerts
|

Survey of trend and factors in perinatal maternal fatigue

Abstract: Few studies have investigated maternal fatigue, particularly fatigue throughout the duration of pregnancy and the postpartum period. The purpose of this study was to explore changes related to maternal fatigue from pregnancy to postpartum and the factors influencing fatigue. This prospective longitudinal study surveyed 197 pregnant women beyond 24 gestational weeks monthly until one month postpartum. The Multidimensional Assessment of Fatigue scale and one question about fatigue were used. Women at late pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
1
31
1
2
Order By: Relevance
“…Social support generally plays an important role in one's health (Negron, Martin, Almog, Balbierz, & Howell, ). Specifically in the early postpartum period when infant care is demanding, social support has been reported to help prevent postpartum depressive symptoms (Third‐person, Mori, Tsuchiya et al., ), increase maternal confidence (Maehara, Mori, Tsuchiya, Iwata, Sakajo, Ozawa et al., ) and manage maternal fatigue (Cheng et al., ; Giallo et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Social support generally plays an important role in one's health (Negron, Martin, Almog, Balbierz, & Howell, ). Specifically in the early postpartum period when infant care is demanding, social support has been reported to help prevent postpartum depressive symptoms (Third‐person, Mori, Tsuchiya et al., ), increase maternal confidence (Maehara, Mori, Tsuchiya, Iwata, Sakajo, Ozawa et al., ) and manage maternal fatigue (Cheng et al., ; Giallo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…() examined 121 mothers in Taiwan from the third trimester to 1 week postpartum and found that the level of fatigue was highest at 1 day postpartum, showing a decrease towards the seventh postpartum day. Another study conducted with 197 mothers in Taiwan from the second trimester to 1 month postpartum reported that the level of fatigue increased from the second to third trimester and remained unchanged until 1 month postpartum (Cheng, Chou, Wang, Tsai, & Liou, ). In Australia, Giallo, Seymour et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Unemployed women and housewives were more depressed than employed women in Malaysia (Zainal et al, ) and Lebanon (Chaaya et al, ). Cheng et al () found that unemployment was a serious problem, with higher levels of fatigue within a period of 24 weeks of gestation and until one month after birth.…”
Section: Introductionmentioning
confidence: 99%